Preventing sexual violence in Vietnam: qualitative findings from high school, university, and civil society key informants across regions - Yount, Kathryn M.; Anderson, Katherine M.; Trang, Quach Thu; Bergenfeld, Irina (BMC public health, 2023)
Background Sexual violence by young men against women is common, but efficacious primary prevention interventions tailored to men are limited in low- and middle-income settings like Vietnam. GlobalConsent, a web-based sexual violence prevention intervention tailored to university men in Hanoi, is efficacious. Implementation research is needed to understand facilitators and barriers to scaling GlobalConsent and prevention programs generally. We conducted qualitative research with key informants from three youth-focused organizational settings to understand the context of implementation in Vietnam. Methods Interviews with university ( n = 15), high-school ( n = 15) and non-governmental ( n = 15) key informants focused on perceptions about sexual violence among young people and prevention programming. Four focus group discussions with 22 interviewed informants, following the Consolidated Framework for Implementation Research, asked about facilitators and barriers to implementing GlobalConsent. Narratives were transcribed, translated, and coded inductively and deductively to identify salient themes. Results Outer-setting influences included greater expectations for sex among young people alongside norms favoring men’s sexual privilege, ostensibly ambiguous and lax laws on sexual violence, government ministries as bureaucratic but potential allies, external subject-matter experts, and the media. Inner-setting influences included variable cultures regarding openness to discuss sexual violence and equitable gender norms, variable departmental coordination, limited funding and ‘red tape’ especially in public institutions, inconsistent student access to technologies, and limited time and competing priorities among students and teachers. Several actors were considered influential, including institutional leaders, human-resource staff, the Youth Union, and student-facing staff. Important characteristics of individuals for implementation included subject-matter expertise, science or social science training, younger age, engagement in social justice related activities, and more open attitudes about sex. Regarding characteristics of sexual violence prevention programming, some participants preferred online formats for busy students while others suggested hybrid or in-person formats, peer education, and incentives. Participants generally accepted the content of GlobalConsent and suggested adding more content for women, ancillary support services, and adapted content for high-school students. Conclusions Implementation of sexual violence prevention programs in youth-focused organizations in Vietnam requires multilevel strategies that connect outer-setting subject-matter experts with supportive inner-setting leaders and student-facing staff to overcome normative and organizational constraints, and thereby, to deliver institution-wide programming.